Publishing, politics, and culture the king's printers in the reign of James I and VI - Rees, Graham; Wakely, Maria (Oxford : Oxford University Press, 2009)
Based on hitherto unexplored and unpublished legal and business records, this study presents a full account of London printing firms in the reign of James I. In particular it examines the businesses of men associated with that crucial instrument of cultural production - the King's Printing House.
Description based on print version record.
Includes bibliographical references and index.
Keywords: King's Printing House (England) -- History; Publishers and publishing -- England -- London -- History -- 17th century; Publishers and publishing -- Political aspects -- England -- London -- History -- 17th century; Great Britain -- History -- James I, 1603-1625.